Assembling Homelessness: A Posthumanist Political Ecology Approach to Urban Nature, Wildlife, and Actor-Networks. (3rd September 2019) - Rose, Jeff; Wilson, Jackson
Abstract: When humans interact with nonhuman nature in seemingly normative ways, through consumption, recreation, admiration, romanticizing, etc., an imperfect but intact binary is often perpetuated; that is, humans are positioned as distinct from nature. Posthumanist political ecology destabilizes the human experience as the sole source of nature-society knowledges. With contributions from actor-network theory and assemblages, posthumanist political ecology provides systems-based analyses where nonhuman actants are underscored within socioenvironmental systems. This research leverages posthumanist political ecology to approach experiences and perspectives concerning unsheltered homelessness, with particular attention to individuals living in urban parks. Using etic and emic accounts, our developed network critically considers nonhuman, wild, and sociopolitical contributions to a contested, dynamic system of unsheltered homelessness. We present posthumanist political ecology as an avenue for leisure research and scholarship to contest problematic binaries concerning nonhuman nature and to more critically address issues of social and environmental injustice.